Bone and joint changes in pneumatic drillers. Issue 3 (June 1977) - Burke, M J; Fear, E C; Wright, V
Abstract : A clinical and radiological survey of 34 men who were pneumatic drillers employed by the North East Gas Board, was carried out to determine the prevalence of osteoarthrosis. Mild osteoarthrosis of the elbows was found in 2 subjects only. Two drillers had radiological evidence of generalized osteoarthrosis elsewhere, and minor degenerative changes were present in the hands of 15 cases. Our findings do not support the view that pneumatic drillers are particularly prone to develop osteoarthrosis.